2019
DOI: 10.1016/j.jnutbio.2019.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics from acorn and sago prevent high-fat-diet-induced insulin resistance via microbiome–gut–brain axis modulation

Abstract: Role of gut microbiome in obesity and type 2 diabetes (T2D) became apparent from several independent studies, indicating that gut microbiome modulators like prebiotics may improve microbiome perturbations (dysbiosis) to ameliorate metabolic derangements. We herein isolate water soluble, non-digestible polysaccharides from five plant based foods (acorn, quinoa, sunflower, pumpkin and sago seeds) and assess their impact on human fecal microbiome and amelioration of high fat diet (HFD)-induced obesity/T2D in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 68 publications
3
102
0
2
Order By: Relevance
“…Consumption of inulin has been shown to prevent metabolic syndrome [36], obesity [3], cardiovascular disease [2], and T2D [4]. In the current study, using pigs as an excellent mimic model for human, the regulating effect of inulin on lipid metabolism was confirmed.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Consumption of inulin has been shown to prevent metabolic syndrome [36], obesity [3], cardiovascular disease [2], and T2D [4]. In the current study, using pigs as an excellent mimic model for human, the regulating effect of inulin on lipid metabolism was confirmed.…”
Section: Discussionsupporting
confidence: 63%
“…A plethora of studies suggest that the dietary fibers, such as inulin, confer health benefits to host metabolism; protect against the metabolic disorder; and reduces the risk of inflammatory bowel diseases [1], cardiovascular diseases [2], obesity [3], and type 2 diabetes mellitus (T2D) [4] in human. Inulin encompasses all β (2→1) linear fructans of varying chain lengths.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Bomhof and Saha found that prebiotic OFS treatment elicited potent effects on the gut microbiota of diet-induced obese rats, thereby reducing adiposity and improving glycemic control as measured by reduced fasting insulin and increased insulin sensitivity [121]. In another study by Ahmadi et al, supplementation with sago and acorn-derived prebiotic fibers was also shown to prevent HFD-induced insulin resistance in mice, reportedly via the combined action of reducing enteric mucosal inflammation and exerting a modulatory effect on hypothalamic energy signaling [122].…”
Section: Anti-obesogenic Effects Of Prebiotic Fibersmentioning
confidence: 98%
“…Equimolar pooled library was sequenced on an Illumina MiSeq platform using 2×300bp reagent kit (Miseq reagent kit v3; Illumina Inc.) for paired-end sequencing. The sequencing quality control was done with on-board Miseq Control Software and Miseq Reporter (Illumina Inc.) and the obtained sequences were de-multiplexed, quality-filtered, clustered and analyzed using QIIME software package (34, 35, 38, 39). Taxonomy classification was performed within QIIME based on 97% sequence similarity to the Greengenes database (38).…”
Section: Methodsmentioning
confidence: 99%